Cooperatives: A standard system - Schwartzman, Yael; Parikh, Tapan S.; Vila, Mario (Technical Centre for Agricultural and Rural Cooperation, 2010)
The Coffee Growers Association of Oaxaca in Mexico uses DigitalICS, a specially developed software program, to help farmers improve the quality of their coffee. Inspectors use cell phones to gather data, which are then posted to password-protected web pages.